Kr–Cl stretching vibration of HKrCl: Matrix-isolation and anharmonic ab initio study: Spectroscopy in Cryocrystals and Matrices - Lignell, Antti; Lundell*, Jan; Pettersson, Mika; Khriachtchev, Leonid; Räsänen, Markku (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
The Kr–Cl stretching vibration of HKrCl molecule is studied. The absorption shows 35Cl and 37Cl isotopic splitting due to natural abundance of the Cl isotopes. The observed Kr–Cl stretchingvibrations of the HKrCl are at 253.1 (35Cl) and 248.3 cm–1 (37Cl). Deuteration of the HKrCl does not cause experimentally a shift of the Kr–Cl stretching frequency. In addition to the Kr–Cl stretching mode, the bending mode of DKrCl is observed at 397.7 cm–1. The vibrational analysis suggests that the Kr–Cl bond show, in addition to ionic, some covalent character. Anharmonic ab initio calculations are employed to verify vibrational properties of various isotopologues of HKrCl.